Jesus van Nasaret se bevrydende visie vir ’n geweldadige samelewing - Joubert, S. J. (Verbum et ecclesia, 1993)
Jesus of Nazareth’s liberating vision for a violent society All political, economical and religious power in first century Palestine were in the hands of less than 5% of the population. This gave rise to a situation of "social rootlessness" among and different violent responses from many Jewish pedants. Within this society, characterized by "ideological" and physical violence, Jesus of Nazareth proclaimed an encompassing new reality, the Kingdom of God. In this regard He not only offered salvation to the victims of violence, hut also expected a new, violent-free, orientation and code of conduct towards God and all human beings from his followers.